Pengobatan mastitis dengan rivanol - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1987)
ABSTRAK Eighty one quarters of 48 cows suffered from mastitis owned by farmers, members of the Koperasi Warga Mulia in Daerah Istimewa Yogyakarta Province were treated with rivanol. A 1 : 4,000 sterile aqueous solution of rivanol was used. Each quarter was milked dry, and 400 ml of solution was infused and massaged. Ten minutes later, the infusion solution was withdrawn. Of 48 cows, 41 or 83 per cent were cured by one single treatment, and 7 or 17 per cent were cured by two treatments, the second treatment was given one week later after the first one. Of 81 quarters, 64 or 84 per cent were cured by one single treatment, and 13 or 16 per cent by two treatments. It is concluded that the result of the observation of the rivanol therapy on mastitis in cows was convincing, and therefore, the use of rivanol, is -recomended primarily in cases where antibiotics resistence bacteria are present. Keywords: rivanol, antibiotics resistence